The Influence Of Workload, Work Conflict And Work Stress on the Performance Of Sprinter Employees at PT Garuda Express Nusantara in Pekanbaru - Kiki Joesyiana; Agustin Basriani; Desi Susanti (eCo-Buss, 2022)
The progress of a company is very dependent on the human resources it has. Although the various factors needed are available, without the role of humans in it, the company will not be able to operate properly. The quality of employee performance is the main factor and determinant of the success of a company. An employee who has qualified abilities and can act well in certain situations and conditions is an achievement for employee performance. The main benchmark in evaluating the performance of an employee is the ability he/she has. How an employee can accept the workload, understand work conflicts and deal with work stress that is experienced, can indicate the high or low quality of employee performance. The respondents in this study were employees of the sprinter department (courier) at PT Garuda Express Nusantara (J&T Express) Pekanbaru, which was located on Harapan Raya Street. The population in this study was 240 employees and the entire population was sampled using a saturated sampling technique. The analysis technique used was descriptive quantitative. The results of the study conclude that workload, work conflict, and work stress influences the performance of sprinter employees at PT Garuda Express Nusantara (J&T Express) Pekanbaru with an Adjusted R Square value (Coefficient of Determination) of 0.858. It means that the influence of the independent variable (X) namely workload, work conflict, and work stress affects the dependent variable (Y), namely employee performance of 85.8%. Meanwhile, the remaining 14.2% is influenced by other variables which not included in this study